Identification and Quantification of Phytochemical Constituents in Rosa Damascena Flower Extract Via GC-MS and HPTLC - Chauhan, Payal; Wadhwa, Karan; Kalra, Sunishtha; Sachdeva, Himanshu; Singh, Govind (Journal of Neonatal Surgery, 2025)
Rosa damascena, commonly known as Damask rose has garnered significant attention in the fields of horticulture, biochemistry, and pharmacology, primarily due to the captivating fragrance of its flowers and the abundance of biologically active compounds. Roses hold global economic significance, serving as the focal point of a substantial ornamental shrub in flower industry. It is a plant with a rich history of ethnobotanical use and its traditional applications across various cultures, highlighting its therapeutic properties. Historically, different parts of R.damascena have been employed to address a wide range of ailments, including digestive issues, skin conditions, perfumes, fragrances and emotional distress. The plant's diverse phytochemical composition, encompassing essential oils, flavonoids, and phenolic compounds, underpins its pharmacological action. The present research aims to underline the phytochemical screening of R. damascena using physical evaluation following qualitative and quantitative phytochemical analysis using GC-MS and HPTLC. Preliminary phytochemical analysis reveals the presence of glycosides, flavonoids, saponins, tannins, and phenolic compounds. Furthermore, various essential phytoconstituents, including citronellol, á-pinene, d-limonene, geraniol, and caryophyllene, were detected using GC-MS. Quantitative densitometry analysis using HPTLC revealed the presence of geraniol in concentrations of 3.54±0.23 w/w. Overall, these findings suggest that R.damascena consist diverse essential phytochemicals that holds significant potential for further exploration as a valuable medicinal resource, offering a foundation for future pharmacological and therapeutic studies.